Offensive Difference Styles and Technical Situational Variables Between European and South American Elite Football Leagues - Izquierdo, José María; Redondo, Juan Carlos (MHSalud: Revista en Ciencias del Movimiento Humano y Salud, 2022)
We aimed to compare teams’ attack styles in Europe and South America elite football in the two most valued domestic leagues in both continents (Spanish La Liga & English Premier League in Europe, and Argentinian Superliga & Brazilian Série A in South America). For this purpose, we used a sample of 84 teams and 3,780 cases in 1,214 games. Using an observational tool, we analyzed performance indicators (goals, shots, dribbles, and passes) and attack situations. Effect size (ES) and non-clinical magnitude-based inference (MBI) were used to evaluate uncertainty. Results revealed that European teams scored more goals per game related to fast (ES = 0.35; likely MBI) and positional attack (ES = 0.36; likely MBI). In addition, teams from the European leagues spent more time playing in the opposition third zone of the pitch, performed a higher number of assists (ES = 0.38; likely MBI) and through-ball assists (ES = 0.46; likely MBI) than South American ones. Finally, South American teams made higher numbers of shots out of the box (ES = 1.52, almost certain MBI) and off-target shots (ES = 1.08; almost certain MBI), and they also spent more time playing in the middle third zone (ES = 1.65; almost certain MBI). No differences were identified in set-pieces goals, length passing, and aerial duels. These findings may provide information regarding attack style proﬁles from each continent league. Also, it could be highly beneficial for coaches to be able to continuously design the specific training situations of the offensive process.